Caloric restriction disrupts the microbiota and colonization resistance - von Schwartzenberg, Reiner Jumpertz; Bisanz, Jordan E.; Lyalina, Svetlana; Spanogiannopoulos, Peter; Ang, Qi Yan; Cai, Jingwei; Dickmann, Sophia; Friedrich, Marie; Liu, Su-Yang; Collins, Stephanie L.; Ingebrigtsen, Danielle; Miller, Steve; et al. (Nature (London), 2021)
Diet is a major factor that shapes the gut microbiome 1 , but the consequences of diet-induced changes in the microbiome for host pathophysiology remain poorly understood. We conducted a randomized human intervention study using a very-low-calorie diet (NCT01105143). Although metabolic health was improved, severe calorie restriction led to a decrease in bacterial abundance and restructuring of the gut microbiome. Transplantation of post-diet microbiota to mice decreased their body weight and adiposity relative to mice that received pre-diet microbiota. Weight loss was associated with impaired nutrient absorption and enrichment in Clostridioides difficile , which was consistent with a decrease in bile acids and was sufficient to replicate metabolic phenotypes in mice in a toxin-dependent manner. These results emphasize the importance of diet–microbiome interactions in modulating host energy balance and the need to understand the role of diet in the interplay between pathogenic and beneficial symbionts. Severe caloric restriction in humans leads to reversible changes in the gut microbiota that promote weight loss and the expansion of an enteric pathogen in mice.